Material didáctico y su influencia en el desarrollo de la motricidad gruesa, en estudiantes de educación inicial 2 de la Unidad Educativa “La Ronda” - Galarza Llanos, Liliana Maricela (2023)
The present research work is outlined with the theme "The Influence of Didactic Material and the Development of Gross Motor in students of Initial Education of the “The Round”, Educational Unit, with a sample of 35 students, the Rector and 2 teachers. Quantitative research was applied because we worked with students from the initial area which facilitate determining at what level each student is, including field research which helps us apply the intervention during the academic period 2023-2024 with the purpose of implementing innovative and creative lesson plans that help improve gross motor skills based on specific materials. The importance of providing an adequate environment rich in stimuli to promote learning and the development of motor skills is highlighted. It is mentioned that teachers must consider that in the first five years of life it is necessary to use specific materials since they are in the pre-operational stage. Considering the variables of the subject provided as Didactic Materials and Gross Motor Skills. The research concludes that the use of didactic materials significantly affects the development of gross motor skills in children in initial education.